On the asymmetric relation between inflation and growth in Mexico: A NARDL approach - José Carlos Trejo-García; Ramón Valencia-Romero; María De Lourdes Soto-Rosales; Francisco Venegas-Martínez (Economies, 2023)
The effects of various geopolitical tensions, conflicts between countries and the global post-pandemic COVID-19 have caused an acceleration in the price level in many countries around the world. This research focuses on Mexico since its monetary policy has created intricate interactions between inflation and growth in the short and long term, maintaining recently one of the highest real interest rates in Latin America (on average 5.75% vs. the US 2.3%). This paper examines the asymmetric link between the National Consumer Price Index and the Global Economic Activity Index in Mexico during the period 1994-2023. To do this, a Nonlinear Autoregressive Distributed Delay (NARDL) model is used with monthly data, which will allow the relationship between both variables to be more adequately investigated. The main empirical finding is that upward or downward shocks to the consumer price index have caused different effects in magnitude and sign on economic growth over time. Finally, several reasonable, practical, and feasible recommendations are provided for the design of the monetary policy considering non-linear effects.
Keywords: 330; inflation dynamics; economic growth; non-linear asymmetric cointegration models